Kajian Strukturalisme dalam Puisi Surat dari Ibu Karya Asrul Sani - Syarifah Rahmah; Hidayah Budi Qur'ani (ESTETIK : Jurnal Bahasa Indonesia, 2021)
This study uses the object of the literary work of poetry "Surat Dari Ibu", by Asrul Sani by using structuralism studies. The purpose of this study is to describe the physical elements and mental elements as a whole which allows to provide new knowledge to the reader. This study uses a qualitative approach to the method of content analysis in poetry. The results obtained in the physical structure of the poem there are 2 dictions related to the choice of words used by the poet. Images / images found 3 images related to the human senses. In concrete words there are 2 related to the overall meaning of the word. There are 2 styles of language, namely comparative figure of speech and affirmation figure of speech. Rima uses free rhyme in his poetry. The last physical element is typography, the poet uses typography in upper and lower case letters and full punctuation in his poetry. The inner element contained in the poem Surat Dari Ibu, Asrul Sani's first work, is the theme of finding a stanza related to the problems in poetry. Based on the tone found 2 tones. The inner element in feeling is found to be a sense of emotion and hope from a mother in the poem Surat Dari Ibu, by Asrul Sani. The last inner element is the mandate, there is one message that the poet wants to convey through his poetry